2017
DOI: 10.1108/ijot-02-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Major trends in the use of occupation as therapy in Ireland 1863-1963

Abstract: Purpose-Major gaps exist in the documented history of occupational therapy in Ireland. The purpose of this paper is to contribute to filling these gaps by providing an overview of three major transitions in Irish occupational therapy in the century preceding the opening of St. Joseph's College of Occupational Therapy in 1963. Research on occupational therapy's past is valuable not only for recording and commemorating key events and individuals but also for allowing reflection on and questioning of contemporary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…The conflicting perspectives on craft as therapy described in the previous paragraph were partially due to participants' efforts to distinguish themselves from existing pre-professional workers and elevate occupational therapy's status. The findings of this study reveal relationships with pre-professional workers that were challenging but sometimes respectful and positive, which further reflects the findings of Alaszewski and Meltzers (1979) and the literature reviewed in Pettigrew et al (2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The conflicting perspectives on craft as therapy described in the previous paragraph were partially due to participants' efforts to distinguish themselves from existing pre-professional workers and elevate occupational therapy's status. The findings of this study reveal relationships with pre-professional workers that were challenging but sometimes respectful and positive, which further reflects the findings of Alaszewski and Meltzers (1979) and the literature reviewed in Pettigrew et al (2017).…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to findings from the mid-1980s by Williams et al (1987), who identified that occupational therapists did not use crafts and other diversional treatment in order to maintain their image with other professionals. This is commensurate with occupational therapy's ambivalent relationship with craft and diversion; however, diversional occupations have also been proposed to have significant therapeutic value (Friedland, 1988) and had a significant therapeutic role during World War I (Pettigrew et al, 2017). Engagement and participation in meaningful occupation is currently a key concern in occupational science and occupational therapy (Morris and Cox, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Eamon O'Sullivan started writing his textbook of occupational therapy in 1935; when H.K. Lewis published it in 1955, it was one of the first European psychosocial textbooks on occupational therapy (Pettigrew et al, 2017). It is evident that his book was a success, selling at least 1000 copies (O'Sullivan, 1965(O'Sullivan, /2007c.…”
Section: Academic Contribution To Occupational Therapy and Academic Rmentioning
confidence: 99%
“…These developments were led by psychiatrists who advocated and supported occupational therapy. Professionally qualified occupational therapists did not begin to practise in Ireland until the late 1940s, so early departments were staffed by nurses, attendants and/or craft teachers (Pettigrew, Robinson, Dunne and O’Mahoney, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases illustrate the relevance of history. During the twentieth century, tuberculous, poliomyelitis and HIV-AIDsweresignificant in the development ofthe profession in South Africa (Concha, 2014), Ireland (Pettigrew et al, 2017a), Israel , Mexico (Cascajares, 1998) and Mozambique (Martins, 2016). In March 2020, the World Health Organisation declared the outbreak of coronavirus (Covid-19) as a global pandemic.…”
Section: Introduction: Histories Mattermentioning
confidence: 99%